Synthesis and Spectral Characterization of Organometallic Derivatives of Palladium(0), Platinum(0), Rhodium(I) and Iridium(I) with Mixed-Ligands - Pandey, R.N.; Gautam, K.V. (Asian Journal of Chemistry, 2011)
Some new organometallic derivatives of Pd(0), Pt(0), Rh(I) and Ir(I) have been prepared and characterized using Wilkinson catalyst, Malatesta compounds and Vaska catalyst by the ligand substitution reaction with dibenzyl sulphide in benzene. The possible structure of all the isolated products have been assigned by elemental analyses, IR, UV-VIS, 1H NMR spectra and other physico-chemical methods.